Positives and negatives of social housing - Urban, David; Hricová, Alena (Journal of Nursing, Social Studies and Public Health, 2021)
The objective of this paper is to analyze the positive and negative experiences of persons living in social housing who have also experienced living in excluded locations. One of the main goals of social housing in the Czech Republic is to increase the access to stable living conditions for families living in unstable or unsuitable conditions (primarily in socially excluded locations). Data is interpreted via interviews with people who – before they gained access to social housing – lived in socially excluded locations. The interviews were processed via open coding. The informants pointed out some positive aspects of social housing, such as the quality of the housing, the price, and the form of paying rent. They also appreciated the existence of a rental agreement, the security of housing, and good relations with their neighbours. The negative aspects of social housing mentioned were primarily issues with the system: the length of the process and lack of social housing apartments. Housing is an area that needs to be addressed first. There is the issue of the unresolved legislature about social housing and an insufficient number of social housing apartments.